ANALISA KARAKTERISTIK DAN STABILITAS MARSHALL ASBUTON LGA 50/30 UNTUK LASTON LAPIS AUS ASBUTON BUTIR (AC-WC ASB. BUTIR) - Listia Ayu Ningrum; Soedarsono Soedarsono; Hermin Poedjiastoeti (Pondasi, 2025)
Asphalt use for road construction is 1,2 million tons a year, domestic production only supplied 0.6 million tons the remaining needs are supported by imports. Asbuton has been uknwon for better adhesive quality than regular oil asphalt. The research aims to find the Marshall stability value by observing the characteristics of Asbuton LGA 50/30 for Asphalt Concrete-Wearing Course Asbuton Granular (AC-WC Asb. Granular) with 5 (five) different Asbuton variants and to find the cost difference in the production of Asphalt Concrete-Wearing Course Asbuton Granular (AC-WC Asb. Granular) compared to the production cost of AC-WC oil asphalt using experimental research methods. The characteristics of Asphalt Concrete-Wearing Course Asbuton Granular (AC-WC Asb. Granular) are higher than AC-WC from regular oil asphalt; visually, the AC-WC with Asbuton addition results in a matte color mixture compared to AC-WC Granular with oil asphalt which Asphalt Concrete-Wearing Course Asbuton Granular has a darker and more glossy black color. From the samples that have been tested, at optimum asphalt content level 6% and the amount of Asbuton used at 7.5%, the Marshall results are: VIM 4.51%, VFB 73.76%, Marshall Stability 1,614 Kg, Flow 2.6 mm, MQ 601.3 Kg/mm, and Residual stability after 24-hour immersion 92.79%. Using Asbuton in the mixture for Laston AC-WC can save production costs by 1.33%.